2021
DOI: 10.3390/ijms22031200
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Role of Sestrin2 in Atherosclerotic and Cardiac Diseases

Abstract: Atherosclerotic disease, such as coronary artery disease (CAD), is known to be a chronic inflammatory disease, as well as an age-related disease. Excessive oxidative stress produced by reactive oxygen species (ROS) contributes to the pathogenesis of atherosclerosis. Sestrin2 is an anti-oxidant protein that is induced by various stresses such as hypoxia, DNA damage, and oxidative stress. Sestrin2 is also suggested to be associated with aging. Sestrin2 is expressed and secreted mainly by macrophages, endothelial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…Ma et al reported that inflammation reduced CD31 expression and increased α-SMA and collagen I expression, which are important markers for cardiac EndMT. They also found that inflammatory stress, including shear stress, oxidative stress and oxidized lipoproteins, exacerbates the progression of cardiac fibrosis in high-fat-fed ApoE KO mice via EndMT, suggesting EndMT and inflammation act synergistically to redistribute plasma lipids to cardiac tissues and accelerate the progression of cardiac fibrosis [70]. EndMT has been found to increase vascular inflammation by TAK1 and Twist1 smf promoting the endothelial expression of the inflammatory molecules VCAM-1 and ICAM-1, leading to vascular dysfunction and atherosclerosis [22,71,72].…”
Section: Inflammation and Endmt In Atherosclerosismentioning
confidence: 98%
“…Ma et al reported that inflammation reduced CD31 expression and increased α-SMA and collagen I expression, which are important markers for cardiac EndMT. They also found that inflammatory stress, including shear stress, oxidative stress and oxidized lipoproteins, exacerbates the progression of cardiac fibrosis in high-fat-fed ApoE KO mice via EndMT, suggesting EndMT and inflammation act synergistically to redistribute plasma lipids to cardiac tissues and accelerate the progression of cardiac fibrosis [70]. EndMT has been found to increase vascular inflammation by TAK1 and Twist1 smf promoting the endothelial expression of the inflammatory molecules VCAM-1 and ICAM-1, leading to vascular dysfunction and atherosclerosis [22,71,72].…”
Section: Inflammation and Endmt In Atherosclerosismentioning
confidence: 98%
“…Because a standard definition of age-related diseases (ARDs) has yet to be agreed upon, epidemiologists differentiate between, on the one hand, all non-infectious diseases with a reliance on incidence rates rising exponentially with age, no matter the lifespan, and, on the other hand, the diseases that start in early life and have stable or lowered incidence rates in the elderly [ 3 ]. Given this lack of strict classification, many age-related diseases can be named as ARDs: sarcopenic obesity [ 4 ], homeostasis dysregulation [ 5 ], subfertility [ 6 ], lipodystrophy [ 7 ], sarcopenia [ 8 ], macular degeneration [ 9 ], chronic inflammation [ 10 ], osteoarthritis [ 11 ], endothelial dysfunction [ 12 ], tissue senescence [ 13 ], cancer [ 14 ], atherosclerosis [ 15 ], cardiovascular diseases [ 16 ], chronic kidney disease [ 17 ], stroke [ 18 ], frontotemporal dementia [ 19 ], Alzheimer’s [ 20 ], and Parkinson’s [ 21 ], to mention some. Moreover, many other pathologies can contribute to ARDs: amyotrophic lateral sclerosis, to motoneuronal aging [ 22 ]; mitochondrial dysfunction, to aging as such [ 23 ]; vascular atherosclerosis, to cellular senescence [ 24 ]; hypertension, to vascular aging [ 25 ]; thalassemia, to myelodysplastic syndrome [ 26 ]; cancer, to immune system aging and vice versa [ 27 ]; and circadian rhythm disorder, to aging as such [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Increased Sesn2 expression reportedly protects against hepatic steatosis, attenuates hepatic endoplasmic reticulum stress, and alleviates fibrosis in obese mice ( Park et al, 2014 ; Jegal et al, 2020 ). Moreover, Sesn2 can activate the AMPK pathway and suppress mTOR signaling to attenuate various metabolic disorders, including insulin resistance, mitochondrial dysfunction, and cardiac dysfunction ( Sun X. et al, 2020 ; Kishimoto et al, 2021 ). Based on the previous literature summarized above, we hypothesized that Sesn2 could serve as a novel therapeutic target for various aging- and obesity-associated diseases.…”
Section: Introductionmentioning
confidence: 99%